Effectiveness of Group Guidance Using Nonviolent Communication (NVC) Techniques to Reduce Verbal Abuse Among Students - Radhna Keumala Rangkuti; Ahmad Syarqawi (Journal of General Education and Humanities, 2025)
Schools play a crucial role in shaping students’ psychological well-being, social relationships, and academic performance. This study aims to examine the effectiveness of group guidance services using Nonviolent Communication (NVC) techniques in reducing verbal abuse among eighth-grade students at MTsN 2 Deli Serdang. The research addresses the increasing prevalence of verbal aggression in school settings, which requires systematic intervention through structured counseling strategies. A quasi-experimental, non-equivalent control group design was employed, involving 18 students divided equally into an experimental and a control group. Data were collected using a verbal abuse questionnaire and analyzed using paired-sample t-tests and independent-sample t-tests through SPSS. Results revealed a significant decrease in verbal abuse behavior in the experimental group after receiving NVC-based group guidance (p < 0.001), while no significant changes occurred in the control group. The independent t-test further confirmed significant differences in posttest scores between groups (p < 0.001). These findings indicate that NVC-based group guidance is effective in reducing students’ verbal aggression by promoting empathetic and constructive communication. Overall, the study demonstrates that integrating NVC techniques into school counseling programs can serve as a practical approach to fostering positive communication habits and creating a healthier, more harmonious learning environment.